Mapping Internet Financial Reporting: A Bibliometric Review - Mathew Kevin Bosi; Nelson Lajuni; Mohd Noor Azli bin Ali Khan (Human Resource Management Academic Research Society, 2021)
Internet financial reporting (IFR) has become the center of discussion among practitioners and researchers as the global economy is undergoing a rapid digital transformation, which structures the new concepts in how businesses operate and interact with their stakeholders. Despite the rapid transformation, studies concerning the bibliometric review on IFR are still considered scarce in this so-called "digital era". Thus, the objective of this study is to perform bibliometric analysis on scientific literature published in the field of IFR, particularly from the years 1998 to 2020. The Scopus database was used to gather all the related literature on IFR. Apart from employing SPSS and Microsoft Excel software, we also utilize Publish or Perish software to integrate the data and perform simple analysis before using VOSviewer to perform data visualization. Publication growth, the productivity of research, and citation analysis were reported via standard bibliometric analysis. A total of 96 documents were retrieved based on the keyword search results. The study reveals that the vast majority of articles were written in English and published in journals and conferences. Most of these articles were in the business, management, and accounting fields. The findings of the study also point to future research, whereby the search query should be expanded to other accessible databases, including but not limited to the Web of Science, Google Scholar, and Dimensions, which would possibly contribute to more invaluable results.